Transparency and accountability mechanisms for disaster management funds: A case study - Liswanty, Ina; Prabowo, Hendi Yogi (Journal of Contemporary Accounting, 2021)
This research was conducted to analyze the improvement in the transparency and accountability mechanism for the management of drought disaster relief funds in the cultural aspect. This research was conducted in the Yogyakarta Special Region Fast Response Foundation (ACT DIY) which is engaged in the management of disaster aid funds. The research method used was a qualitative method with primary data by interviews, and secondary data in the form of documents obtained through the official website of ACT, social media, and supporting documents directly requested from the source. The data analysis techniques employed were three stages of coding; initial coding, axial coding, and selective coding, and continued by constructing analytical maps, matrix coding queries, and framework matrices. In order to manage, integrate, test, and search for patterns and more detailed relationships, NVivo 11 software was employed for assistance. The results demonstrate that understanding community culture is a complementary value in improving the transparency and accountability of a foundation which can be a new strategy in improving transparency and accountability in similar foundations and especially the Yogyakarta Special Region's ACT. Similar research by extending community culture through different cultural theories can also be an opportunity for future research to improve transparency and accountability in managing disaster relief funds.